Perlindungan Hukum Rahasia Dagang atas Informasi Bisnis dalam Perjanjian Kerja Di Kota Denpasar (Studi: Street Food Hoki Takoyaki) - Rivaldo Avianto; Ni Luh Mahendrawati; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2022)
The business world is very vulnerable to legal problems such as leaking and theft of a recipe that is kept secret by the owner. This research aims to find out the legal efforts to maintain trade secrets on Hoki Takoyaki street food in Denpasar city, namely through employment contracts after knowing the legal consequences of trade secret violations in Hoki Takoyaki street food in employment agreements in the city of Denpasar, namely illegal acts in the field of Intellectual Property Rights that have been regulated in Law No. 30 of 2000 concerning Trade Secrets. This study uses empirical research types. The data used is secondary data consisting of primary, secondary, and tertiary legal materials. Data collection techniques with literature studies, observations, and interviews. The data obtained is qualitatively analyzed using descriptive methods of analysis. The results of the study showed a finding that is considered a trade secret if there is an effort to maintain confidentiality made by the owner. In a company where there is a violation of trade secrets, the State provides legal protection for those harmed by the leak by issuing Law No. 30 of 2000 on Trade Secrets.